2019
DOI: 10.1021/acs.energyfuels.9b00508
|View full text |Cite
|
Sign up to set email alerts
|

Improved Gas–Solids Mass Transfer in Fluidized Beds: Confined Fluidization in Chemical-Looping Combustion

Abstract: Fluidized bed processes with reactive bed material have become increasingly popular as research topics, with applications such as chemical-looping technologies, oxygen carrier aided combustion, and fluidized bed gasification being extensively investigated. When used at commercial scale the performance of such processes may be limited not by gas–solid reactivity, but by mass transfer of reactants from bubbles to the emulsion phase. In an effort to break down the two-phase flow structure, and thereby increase th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…In the case of syngas, the inlet and outlet flows of H 2 must be accounted for as water is condensed prior to the analysis. Thus, eqs and can be obtained from a mass balance between inlets and outlets The conversion of H 2 is calculated using eq …”
Section: Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of syngas, the inlet and outlet flows of H 2 must be accounted for as water is condensed prior to the analysis. Thus, eqs and can be obtained from a mass balance between inlets and outlets The conversion of H 2 is calculated using eq …”
Section: Materials and Methodsmentioning
confidence: 99%
“…Previous studies showed that, in a BFB, the mass transfer rate of gas between the bubble and emulsion phase decreases with an increase in the bubble size. While small bubbles are desirable for effective mass transfer, large bubbles can have the opposite effect by causing gas bypass and slugging . One effective method to eliminate bubble growth in BFBs is applying the concept of packed fluidized beds. ,, In this method, inert stagnant packings of a much larger size than the fluidized particles are applied to inhibit bubble growth and breakdown larger bubbles into smaller bubbles, as illustrated in Figure .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The air density (ρ air ) is assumed to be negligible compared to the particle density (ρ p ) and the voidage of the fixed bed (ε f ixed ) is assumed to be 0.4, whereas the voidage in the bubbling bed (ε BFB ) is assumed to be 0.6. Sand could be assumed to be an inert bed material, but to make sure that this is the case, the reactivity of sand was tested in a separate experiment at high temperature where syngas was mixed with nitrogen [29]. This experiment showed that the sand was inert and did not show any tendencies of gas-solid reactions with the CO or H2.…”
Section: Reactor Systemmentioning
confidence: 99%